ASSESSMENT AND IMPROVEMENT OF FOOD SUSTAINABILITY AND THE FACTORS INFLUENCING CONSUMPTION PATTERNS - Cătălin Răzvan VÎNTU; George UNGUREANU; Bianca Antonela UNGUREANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study focuses on the assessment and enhancement of food sustainability, exploring the multifaceted factors that shape consumption patterns. In a world marked by growing concerns about food security and environmental sustainability, understanding the dynamics of food consumption becomes paramount. Through a comprehensive analysis, this research delves into various dimensions of food sustainability, encompassing environmental impact, social equity, and economic viability.The methodology involved evaluating primary food sustainability indicators and concluded with a social survey analysis. Forecasts for the average daily food consumption per capita were interpreted. The study examined the Global Food Security Index (GFSI) in Europe, reflecting food access levels and the population’s ability to secure adequate, safe, and nutritious food. The aim was to identify the most precise and statistically valid forecast method. Romania ranks 23rd in the GFSI overall score, which is improving. It stands 25th in accessibility, 2 st in food availability, and also 2 st in quality and security. While the overall score, accessibility, and availability show positive trends, quality and safety exhibit a decline. The critical analysis led to recommendations for a unified strategy to boost food sustainability.